PENGARUH MODEL DISCOVERY TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 66 PONTIANAK KOTA - Niko, Niko; Kresnadi, Hery; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is "How to influence  discovery on learning outcomes of IPA student grade V Primary School?". This research aims to analyze the influence of  discovery on the outcome of science students grade V Primary School.This study used experimental methods, with the form of quasi Experimental Design. The population in this study is all students of grade V Primary Schoolwhich amounted to 64 people. The sample in this study was a VA class student numbering 32 people. The data collection technique used in this research is a measurement technique with the tools used is a double choice written test as much as 45 questions. Based on data analysis obtained average final test result student of experimental class of 75,03 and average final test result of control class students of 70,53. After conducted test T acquired Tcount of 1,7108 whereas Ttable of 1,6706 it turns out Tcount ≥ ttable or 1.7108 ≥ 1.6706 which means there is influence of  discovery of learning results of IPA students in grade V Primary School. From the effect of calculation result is obtained by 0.38 with the criteria classified as medium. This means the application of discovery learning gives a moderate influence on the outcome of learning IPA students grade V Primary School. Keyword: Influence, Model of Discovery, learning outcomes, natural sciences.